Análises das comparações bioquímicas no soro e exsudato peritoneal de camundongos BALB/c inoculados com cepa cistogênica e não cistogênica de Toxoplasma gondii - Sylvio, Mirian de (2009)
Infection with Toxoplasma gondii occurs throughout the globe, with a prevalence of up to 90% in the population. The physiological changes caused by this parasite are well studied in immunocompromised individuals and in cases of congenital transmission. In immunocompetent individuals the infection is usually asymptomatic and little explored by researchers. Experimental studies follow the pattern of human studies, and there fow mention about the biochemical changes (liver and kidney metabolisms) in the host infected by T. gondii. This study aimed the quantification of hepatic and kidney alterations caused by acute infections by T. gondii (non cystogenic strain – RH) and by chronic infections (cystogenic strain – ME-49). The control group was formed by mice without infection, only submitted to saline stress. Several enzymes were measured in serum and peritoneal exudate of mice infected and control such as: aspartate aminotransferase (AST), alanine aminotransferase (ALT), glutamyltransferase (GGT), alkaline phosphatase (ALP), urea, creatinine and lactate dehydrogenase, using an automated methodology. AST and ALT presented a significative difference in the serum of mice infected with RH strain when compared to controls indicating a destruction of liver cells. The peritoneal exudates did not present significative changes in relation to controls nor did the urea and creatinine levels. The séric lactate dehydrogenase showed gradual changes in all days of the infection in mice peritoneal exudates as early as this change was evident only in the fifth day of infection. All samples of the group infected with ME-49 strain showed changes in serum and peritoneal exudate during all days of analysis. Only ALT peritoneal exudates showed no change during all days of analysis. An increase in urea at all doses was observed, however, creatinine showed a change only within 120 days of infection. The LDH was altered in the serum in all days of analysis. In conclusion, the T. gondii infection may cause hepatic and kidney injuries either when caused by non-cystogenic as by cystogenic strains of the parasite.